Biohydrogen productions from hydrolysate of water hyacinth stem (Eichhornia crassipes) using anaerobic mixed cultures - Sakchai Pattra,; Sureewan Sittijunda, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Response surface methodology (RSM) with central composite design (CCD) was applied to optimize key factors affecting hydrogen production (HP) from diluted acid hydrolysate of water-hyacinth stem (WHS) by heat-treated anaerobic sludge in a batch fermentation process. Key factors affecting namely substrate concentration and initial pH was investigated. The results indicated that substrate concentration and initial pH had significantly effects on HP (p<0.05). A maximum HP hydrogen production rate and hydrogen yield of 182.7 mmol H2/L, 2.81 mmol H2/L h and 0.84 mol H2/mol hexose were obtained under the optimum conditions i.e. substrate concentration of 4.06 g/L and initial pH of 5.81. The total energy production from the fermentative of WHS hydrolysate was 1.97 kJ.